Improving User Engagement of the Livin Mandiri Application: An Analysis of the Role of Gamification and User Experience with User Satisfaction as a Mediator - Maulana Rifky Yudhira; Umi Widyastuti; Meta Bara Berutu (Escalate : Economics and Business Journal, 2026)
The rapid advancement of digital banking services has led financial institutions to strengthen user interaction through user experience and gamification strategies. This study aims to analyze the effect of user experience and gamification on user engagement in the Livin by Mandiri application, with user satisfaction as a mediating variable. This quantitative study used primary data collected through online questionnaires distributed to 234 users in the Jakarta area. Data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS 4 software. The results show that both user experience and gamification significantly influence user satisfaction, while user satisfaction positively affects user engagement. However, user experience and gamification do not directly influence engagement. The study concludes that user satisfaction serves as a crucial mediating factor linking system design and motivational features to sustainable engagement in digital banking services.